(3LGeY GdCUhd dCMGOjK GdQShds - (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO Hf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s ((3OGQ GdMOjK HMeGI GdeYQhaI HHfiGHi GdOe s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ChVM deYGde GdESdGe SHjdkG CeG HYO aEf eHfi gPG GdcJGH Ydi KdGKI CQcGf hGdChd ai GdeHGOF , hGdKGfi ai GdebGUO hGdKGdK ai GdNhGJe s
(3BNQgG (B:s
(3jfJgi HBNQ GdcJGH GdChd ai JaSjQ GdbQBf ef MQa GdJGA (B( (3hai QhGjI bGd (B: (3bGd QShd Gddg Udi Gddg Ydjg hSde (B: (3GdTjWGf NGJe Ydi bdH GHf BOe aEPG GPcQ Gddg NfS , hEPG CZad hShS Je GdeLdO GdChd hgPG ai JaSjQ ShQI GdeYhPJjf s
(3GdfSNI HgG MhGTs
(3bQCgG GHf LeGYI Ydi CHj GdaVd Hf CHj GdOe SfI (B633(3g`s
(3hSeYg CHh GdaVd Ydi eUfag SfI (B606 (3HGdehUd s
(3HBNQgG SeGYGJ cKjQI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdMOjK h GdeUWdMs